Regulasi Pencegahan Tindak Pidana Korupsi Bantuan Dana Keolahragaan Kemenpora Kepada Organisasi Keolahragaan - Samsudin UIA; Efridani Lubis; Slamet Riyanto (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2023)
Sports development is one of the pillars for maintaining health and fitness that can support the productivity of human resources. Law Number 11 of 2022 concerning Sports mandates that Sports has the function of developing physical, spiritual and social abilities as well as forming dignified national character and personality. Sports activities are essentially a miniature of life. It is said so because in sports activities there are many values, in addition to people who carry out sports activities have goals such as for health, pleasure and free time, it is also universally embedded in sports values of struggle, pioneering, cooperation, competition, respect, communication and integration, physical endurance and mental endurance, togetherness, responsiveness, leadership and decision making, honesty and sportsmanship, and others. Sports have become a necessity of life for people of all nations and countries. Therefore, in almost all societies in this world, including in Indonesia, sports activities are a way to balance their spiritual and physical life. Considering that the universal values of sport have positive implications for the formation of an advanced and cultured society, it is only fitting that sport is placed as one of the important priorities in national development. Success in achievement is not obtained suddenly or in an instant way, but through a long process, from achievement to a higher level of achievement, all of which require the involvement of other sports actors as reinforcement. The series of recreational sports activities that form the basis of KORMI's work program can be said to be a form of process. Thus, the activities of many sports organizations are assisted with funds from the Ministry of Youth and Sports. Sports grant funds are actually a form of government support both at the central and regional levels in supporting sports coaching programs implemented by KONI together with the main sports branch organizations. Referring to the findings of the Supreme Audit Agency (BPK) on audit reports both at the central and regional levels on the use of sports grants, corruption as perpetrated by the top leadership, the ministries above, is one of the many major problems we are currently facing. . Corruption is clearly an act that is not commendable that is carried out individually or in groups in an effort to enrich themselves or groups from sources of opinion that are legally illegal. In addition, acts of corruption also harm the noble values of Pancasila as the basis of the state. With the many findings and cases of corruption in sports grant funds above, the government should take firm steps. It is suspected that the problem lies in the lax regulation that is used as the basis for providing these sports grants.